A Bibliometric Analysis of Sustainable Solid Waste Management Technologies using Scopus Database - Bupe G Mwanza (International Journal of Engineering and Management Research, 2024)
A bibliometric analysis of sustainable solid waste management (SSWM) technologies was conducted to establish the hotpots and research shifts based on literature from Science Citation Index (SCI) database from 2010 to 2023 that was retrieved from Scopus database. The research trends and statistics are presented first and then a comprehensive bibilometric analysis using VOSviewer software is performed. The research establishes that, publication output increased between 2020 and 2022 and the Journal of Cleaner Production had the highest number of publications. Between 2017 and 2019 the focus of research on SSWM technologies was towards waste management and sustainable development. The technologies considered during this period were recycling, waste incineration, gasification, anaerobic digestion, and waste to energy, bioenergy and composting. Between 2020 and 2023 the focus was on environmental sustainability and circular economy. The SSWM technologies between 2020 and 2023 focused on resource recovery and pyrolysis.